A Field Experiment on Labor Market Speeddates for Unemployed Workers - Bas van der Klaauw; Lennart Ziegler (Institute of Labor Economics (IZA), 2019)
We conduct a field experiment to evaluate the effectiveness of labor market speeddates where unemployed workers meet temporary employment agencies. Our analysis shows that participation in such events increases immediate job finding by 6-7 percentage points. In the subsequent months, employment effects diminish again, suggesting that vacancies mediated through temporary employment agencies have no long-lasting effect on employment prospects. While the intervention is cost effective for the UI administration, higher labor earnings of treated job seekers do not fully compensate for the decline in benefit payments. Additional survey evidence shows that speeddate participation increases job search motivation and reduces reservation wages.
Keywords: J64; J65; C21; C93; 330; matching events; active labor market policies; randomized experiment; temporary work; job search behavior